Inducible versus constitutive social immunity: examining effects of colony infection on glucose oxidase and defensin-1 production in honeybees. Issue 5 (31st May 2017) - López-Uribe, Margarita M.; Fitzgerald, Andrea; Simone-Finstrom, Michael
Abstract : Honeybees use a variety of defence mechanisms to reduce disease infection and spread throughout the colony. Many of these defences rely on the collective action of multiple individuals to prevent, reduce or eradicate pathogens—often referred to as 'social immunity'. Glucose oxidase (GOX) and some antimicrobial peptides (e.g. defensin-1 or Def1) are secreted by the hypopharyngeal gland of adult bees on larval food for their antiseptic properties. Because workers secrete these compounds to protect larvae, they have been used as 'biomarkers' for social immunity. The aim of this study was to investigate if GOX and Def1 are induced after pathogen exposure to determine whether its production by workers is the result of a collective effort to protect the brood and colony in response to a pathogen challenge. Specifically, we quantified GOX and Def1 in honeybee adults before and after colony-level bacterial infection by American foulbrood ((AFB), Paenibacillus larvae ). Overall, our results indicate that levels of GOX and Def1 are not induced in response to pathogenic infections. We therefore conclude that GOX and Def1 are highly constitutive and co-opted as mechanisms of social immunity, and these factors should be considered when investigating immunity at the individual and colony level in social insects.